BEHAVIOURAL SEASONAL ANOMALIES ON THE STOCK EXCHANGE – VERIFICATION OF THE JANUARY EFFECT ON THE WSE IN WARSAW - Tomasz Pawlonka; Paweł Sypniewski (Polityki Europejskie, Finanse i Marketing, 2023)
Practice and empirical observations prove that achieving above-average returns on the stock market is possible. It is possible to achieve both higher and lower returns than those resulting from the fundamental value of the companies being valued. This condition is affected by anomalies that make the market ineffective. Numerous studies in behavioural finance show that the causes of market inefficiency are to be found in the incomplete rationality of investors. Numerous deviations of investor behaviour from the homo economicus model result from their cognitive and motivational limitations. Sometimes the mistakes of an individual investor are systematic – such systematic and massive errors take the form of heuristics that can influence the magnitude of market anomalies, including the occurrence of calendar effects. One of the best-known calendar anomalies is the January Effect. The January Effect is characterised by an increase in stock prices in January, andthe occurrence of the January Effect is expressed by the fact that the returns in January are the highest of the entire year. The research conducted on the Warsaw Stock Exchange confirmed the presence of the January Effect in small- and medium-sized companies. During the research, the presence of other calendar effects (related to the months of June and October) was also diagnosed.